Comparison of germline mutations in African American and Caucasian men with metastatic prostate cancer. Issue 7 (1st April 2021) - Ledet, Elisa M.; Burgess, Earle F.; Sokolova, Alexandra O.; Jaeger, Ellen B.; Hatton, Whitley; Moses, Marcus; Miller, Patrick; Cotogno, Patrick; Layton, Jodi; Barata, Pedro; Lewis, Brian E.; Nakazawa, Mari; et al.
Abstract: Background: The goal of this study is to evaluate germline genetic variants in African American men with metastatic prostate cancer as compared to those in Caucasian men with metastatic prostate cancer in an effort to understand the role of genetic factors in these populations. Methods: African American and Caucasian men with metastatic prostate cancer who had germline testing using multigene panels were used to generate comparisons. Germline genetic results, clinical parameters, and family histories between the two populations were analyzed. Results: A total of 867 patients were included in this retrospective study, including 188 African American and 669 Caucasian patients. There was no significant difference in the likelihood of a pathogenic or likely‐pathogenic variants (PV/LPVs) between African American and Caucasian patients ( p  = .09). African American patients were more likely to have a variant of unknown significance than Caucasians (odds ratio [OR] = 1.95; p  < .0001). BRCA1 PV/LPVs were higher in African Americans (OR = 4.86; p  = .04). African American patients were less likely to have a PV/LPV in non‐BRCA DNA repair genes (OR = 0.30; p  = .008). Family history of breast (OR = 2.09; p  = .002) or ovarian cancer (OR = 2.33; p  = .04) predicted PV/LPVs in Caucasians but not African‐Americans. This underscores the limitations of family history in AA men and the importance of personal history to guide germline testing in AA men. Conclusions: In metastatic prostate cancer patients, PV/LPVs of tested genes did not vary by race, BRCA1 PV/LPVs were more common in the African American subset. However, PV/LPVs in non‐BRCA DNA repair genes were less likely to be encountered in African Americans. Family history associated with genetic testing results in Caucasians only.